2020
DOI: 10.1038/s41598-020-59618-8
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic differences in neuroimaging markers and cognition in Asians, a population-based study

Abstract: We examined interethnic differences in the prevalence of neuroimaging markers of cerebrovascular and neurodegenerative disease in 3 major Asian ethnicities (Chinese, Malays, and Indians), as well as their role in cognitive impairment. 3T MRI brain scans were acquired from 792 subjects (mean age: 70.0 ± 6.5years, 52.1% women) in the multi-ethnic Epidemiology of Dementia In Singapore study. Markers of cerebrovascular disease and neurodegeneration were identified. Cognitive performance was evaluated using Mini Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…EDIS is a subsample of population-based study (i.e., Singapore Epidemiology of Eye Diseases) that identifies the prevalence and risk factors for cognitive impairment and dementia. Recruitment of participants and data collection methodology were described in previous study [ 25 ]. Briefly, the EDIS participants consist of Singaporean citizens or permanent residents from three ethnic groups (i.e., Chinese, Malay, and Indian) aged≥60 years.…”
Section: Methodsmentioning
confidence: 99%
“…EDIS is a subsample of population-based study (i.e., Singapore Epidemiology of Eye Diseases) that identifies the prevalence and risk factors for cognitive impairment and dementia. Recruitment of participants and data collection methodology were described in previous study [ 25 ]. Briefly, the EDIS participants consist of Singaporean citizens or permanent residents from three ethnic groups (i.e., Chinese, Malay, and Indian) aged≥60 years.…”
Section: Methodsmentioning
confidence: 99%
“… 55 In Asia itself, Wong and coworkers found that there were ethnic differences of neurodegenerative diseases neuroimaging markers in three major Asian ethnicities, which are Chinese, Malays, and Indians, with a higher burden of neurodegenerative markers (cognitive performance, intracranial stenosis, and cortical atrophy) in Malays and Indians than in the Chinese. 56 …”
Section: Neurodegenerative Diseases In Asia Ethnicity Has Greater Imp...mentioning
confidence: 99%
“…55 In Asia itself, Wong and coworkers found that there were ethnic differences of neurodegenerative diseases neuroimaging markers in three major Asian ethnicities, which are Chinese, Malays, and Indians, with a higher burden of neurodegenerative markers (cognitive performance, intracranial stenosis, and cortical atrophy) in Malays and Indians than in the Chinese. 56 As a consequence of population aging, it is predicted that in 2050 there will be 2.7 times more dementia cases than in 2019. 57 Dementia prevalence in Asia has been known previously to be lower than dementia prevalence in Western.…”
Section: Neurodegenerative Diseases In Asia Ethnicity Has Greater Imp...mentioning
confidence: 99%
“…Previous epidemiological studies have highlighted that overall dementia prevalence can vary substantially across different ethnic groups and geographical regions ( 149 ). These differences in dementia prevalence rates have been attributed to different susceptibility to pathological brain changes in each ethnicity ( 150 ). In this sense, neuroimaging research in Brazil should consider these aspects.…”
Section: Peculiarities and Challenges That Hinder Neuroimaging Dementmentioning
confidence: 99%